Determination of Antimicrobial and Antioxidant Activity of Alchemilla alpina L. - İnci, Şule; Eren, Ayşe; Kırbag, Sevda (My University, 2021)
Alchemilla genus, which belongs to the Rosaceae family, is a medicinal plant used for various\rpurposes among the people. Species of this genus are known in Turkish folk medicine as lion claw\ror hazelnut grass. Especially, they are used mainly women’s illnesses, in gastritis, anti-\rinflammatory, as carminative, and in the treatment of wound. Besides the antimutagenic effect of\rAlchemilla alpina L., its above-ground parts are used for antimycotic purposes in the form of tea or\roral care water. In this study, it has been aimed to determine the antimicrobial effect of the above-\rground parts of Alchemilla alpina extracts obtained from methanol, ethanol and chloroform and the\rantioxidant activity of different concentrations of the extract obtained from methanol. The\rantimicrobial activity of methanol, ethanol and chloroform extracts of the above-ground parts of A.\ralpina has been determined according to disk disc diffusion method. In the results obtained have\rbeen showed that these extracts inhibited the growth of some bacteria (Staphylococcus aureus\rATCC25923, Escherichia coli ATCC25322, Klebsiella pneumoniae ATCC700603, Bacillus\rmegaterium DSM32) and yeasts (Candida albicans FMC17 and Candida glabrata ATCC66032) at\rdifferent rates (8-23 mm). The antioxidant activity of different concentrations (1.25, 2.5, 5 and 10\rmg/ml) of the above-ground parts of A. alpina extract obtained from methanol has been determined\raccording to the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity method. In the\rresults obtained, it has been observed that the effect of removing DPPH radical of A. alpina\rincreased depending on increasing concentrations.
Keywords: Mikrobiyoloji; Gıda Bilimi ve Teknolojisi